Genetic analysis of dicyemid infrapopulations suggests sexual reproduction and host colonization by multiple individuals is common - Flegrová, Tereza (Jihočeská univerzita, 2022)
This study explores the infrapopulation structure of Dicyema moschatum in its host Eledone moschata with the use of microsatellite markers. In order to assess the infrapopulation diversity, set of eight microsatellite markers was selected and respective oligonucleotides were designed for this population genetics study. Fragmentation method was used to analyze various microsatellite markers and the results were analyzed in bioinformatic programs that focus on standard population genetic metrics. Obtained results proved to provide new information about D. moschatum mating system and infection strategy.
Genetic analysis of dicyemid infrapopulations suggests sexual reproduction and host colonization by multiple individuals is common
Keywords: mikrosatelity; populační diverzita; dicyemida; eledone moschata; dicyema; populační genetika; microsatellites; population diversity; dicyemida; eledone moschata; dicyema; population genetics